1999
DOI: 10.1596/1813-9450-2278
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity Constraints and Investment in Transition Economies: The Case of Bulgaria

Abstract: We use Bulgarian firm-level data to investigate the impact of liquidity constraints on investment performance. Internal funds are an important determinant of investment in most industrialized countries. We test whether internal funds are important for firm investment during the current transition process in Bulgaria. We use a simple accelerator model of investment to test whether liquidity constraints are relevant in the case of Bulgaria. Our estimations are based on data for the period 1993-95, prior to the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 6 publications
4
29
0
Order By: Relevance
“…This problem would be further exacerbated if financial systems are not functioning properly. As Konings et al (2003) and Budina et al (2000) show this appears to be the case of the European Union. Relative to firm growth rates, the mean value is 0.51%.…”
Section: Data and Summary Statisticsmentioning
confidence: 89%
“…This problem would be further exacerbated if financial systems are not functioning properly. As Konings et al (2003) and Budina et al (2000) show this appears to be the case of the European Union. Relative to firm growth rates, the mean value is 0.51%.…”
Section: Data and Summary Statisticsmentioning
confidence: 89%
“…1 This problem would be further exacerbated if financial systems are not functioning properly and studies would indicate that this appears to be the case in CEE , Gros and Suhrchke, 2000, Budina Garretsen and de Jong, 2000and Anderson and Kegels, 1997. However, although Slovenia has made progress in key areas, it lags behind some of the most advanced transition countries when it comes to implementing some specific reforms, namely financial sector development.…”
Section: Introductionmentioning
confidence: 99%
“…In the rest of the paper, we exploit these observed dissimilarities and try to disentangle the correlation between a more formal 10 See Kornai (1979Kornai ( , 1986) for a discussion on soft budget constraints. A series of papers have found that financial constraints were absent or limited in some transition countries and have argued this was due to the persistence of soft budget constraints (see, for example, Budina et al, 2000;Lizal and Svejnar (2002);and Konings et al, 2003). measure of financing constraints and productivity.…”
mentioning
confidence: 99%